The analyses of the competition process for technology acquisition: Errors and advices - Broniukaitis, Romualdas (Information & Media, 1997)
The article deals with the analyses of materials of competitions organized in Lithuania. The author indicates main errors and formulates the advice for the future.
Keywords: -